First‐in‐human use of a marine oxygen carrier (M101) for organ preservation: A safety and proof‐of‐principle study. Issue 6 (21st February 2020) - Le Meur, Yannick; Badet, Lionel; Essig, Marie; Thierry, Antoine; Büchler, Matthias; Drouin, Sarah; Deruelle, Charles; Morelon, Emmanuel; Pesteil, Francis; Delpech, Pierre‐Olivier; Boutin, Jean‐Michel; Renard, Felix; et al.
Abstract : The medical device M101 is an extracellular hemoglobin featuring high oxygen‐carrying capabilities. Preclinical studies demonstrated its safety as an additive to organ preservation solutions and its beneficial effect on ischemia/reperfusion injuries. OXYgen carrier for Organ Preservation (OXYOP) is a multicenter open‐label study evaluating for the first time the safety of M101 added (1 g/L) to the preservation solution of one of two kidneys from the same donor. All adverse events (AEs) were analyzed by an independent data and safety monitoring board. Among the 58 donors, 38% were extended criteria donors. Grafts were preserved in cold storage (64%) or machine perfusion (36%) with a mean cold ischemia time (CIT) of 740 minutes. At 3 months, 490 AEs (41 serious) were reported, including two graft losses and two acute rejections (3.4%). No immunological, allergic, or prothrombotic effects were reported. Preimplantation and 3‐month biopsies did not show thrombosis or altered microcirculation. Secondary efficacy end points showed less delayed graft function (DGF) and better renal function in the M101 group than in the contralateral kidneys. In the subgroup of grafts preserved in cold storage, Kaplan‐Meier survival and Cox regression analysis showed beneficial effects on DGF independent of CIT ( P  = .048). This study confirms that M101 is safe and shows promising efficacy data. Abstract : The evaluation of a marine oxygen carrier for organ preservation (OXYOP) study evaluates the safety and performance of the medical device M101 used as an additive to preservation solution for the prevention of ischemia‐reperfusion injuries in renal transplantation.